2016
DOI: 10.1002/2016gc006487
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high sensitivity moment magnetometry of geological samples using magnetic microscopy

Abstract: Useful paleomagnetic information is expected to be recorded by samples with moments up to three orders of magnitude below the detection limit of standard superconducting rock magnetometers. Such samples are now detectable using recently developed magnetic microscopes, which map the magnetic fields above room‐temperature samples with unprecedented spatial resolutions and field sensitivities. However, realizing this potential requires the development of techniques for retrieving sample moments from magnetic micr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 60 publications
(99 reference statements)
1
50
0
Order By: Relevance
“…The sample magnetic field is generated by field sources, such as current densities or magnetic dipoles, with either known or unknown distributions. Measurement of the sample magnetic field can be used for the inverse problem of estimating an unknown source distribution under certain conditions [40][41][42]. The form of the sample magnetic field in terms of its sources is…”
Section: Sample Fieldsmentioning
confidence: 99%
“…The sample magnetic field is generated by field sources, such as current densities or magnetic dipoles, with either known or unknown distributions. Measurement of the sample magnetic field can be used for the inverse problem of estimating an unknown source distribution under certain conditions [40][41][42]. The form of the sample magnetic field in terms of its sources is…”
Section: Sample Fieldsmentioning
confidence: 99%
“…Thus, previous studies had to sacrifice temporal resolution that speleothems could potentially offer. Whereas scanning SQUID microscopy (SSM) can image very weak magnetic fields above natural geologic sample with a high spatial resolution of ~ 100 µm (e.g., Lima and Weiss, 2016;Oda et al, 2016), which could likely solve the problem of weak magnetism associated with Speleothem based paleomagnetic studies. To date, only a few preliminary studies addressing the using SSM on speleothems have been reported (e.g., Myre et al, 2019;Feinberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to calculate with confidence the magnetization of small particles generating discrete, isolated anomalies (i.e., de Groot et al, ; Lima & Weiss, ; Weiss et al, ). Here, we investigated the small‐scale spatial variation of the remanent magnetization in large magnetite grains (>100 μm).…”
Section: Introductionmentioning
confidence: 99%